PERSPECTIVES OF 2D AND 3D MAPPING OF ATMOSPHERIC POLLUTANTS OVER URBAN AREAS BY MEANS OF AIRBORNE DOAS SPECTROMETERS - Giovanelli G.; Palazzi E.; Petritoli A.; Bortoli D.; Kostadinov I.; Margelli F.; Pagnutti S.; Ravegnani F.; Trivellone G.; Premuda M. (My University, 2006)
In the field of air quality control, optical remote sensing systems can measure the spatial distribution of gas pollutants, offering numerous advantages over conventional networks of in situ analysers. We propose some innovative solutions in the field of DOAS (Differential Optical Absorption Spectroscopy) remote systems, utilizing diffuse solar light as the radiation source. We examine the numerous potentialities of minor gas slant column calculations, applying the «off-axis» methodology for collecting the diffuse solar radiation. One of these particular approaches, using measurements along horizontal paths, has already been tested with the spectrometer installed on board the Geophysica aircraft during stratospheric flights up to altitudes of 20 km. The theoretical basis of these new measurement techniques using DOAS remote sensing systems are delineated to assess whether low altitude flights can provide 2D and 3D pollution tomography over metropolitan areas. The 2D or 3D trace gas total column mapping could be used to investigate: i) transport and dispersion phenomena of air pollution, ii) photochemical process rates, iii) gas plume tomography, iv) minor gas vertical profiles into the Planetary Boundary Layer and v) minor gas flux divergence over a large area.
Keywords: AIRCRAFT MEASUREMENTS OF ATMOSPHERIC TRACE GASES; ATMOSPHERIC POLLUTANTS TOMOGRAPHY; DOAS APPLICATIONS IN URBAN AREAS